PROJECT BASED LEARNING IN TRANSLATION CLASS - Apandi, Apandi; Afiah, Devi Siti Sihatul (Universitas Swadaya Gunung Jati, 2019)
PROJECT BASED LEARNING IN TRANSLATION CLASSApandiProdi Pendidikan Bahasa Inggris, FKIP Unswagati CirebonEmail: aapandi5@gmail.comDevi Siti Sihatul AfiahProdi Pendidikan Bahasa Inggris, FKIP Unswagati Cirebon AbstractThis study aims to identify student learning experiences in the Indonesian-English translation class. This study uses a case study approach with data collection methods in the form of observations, interviews and questionnaires. Observations are made to obtain data sources from direct sources. Interviews were conducted to find out whether the places visited had historical stories, legends or folktales that could be translated into English, and also to find out the obstacles or challenges faced during learning using PBL. A questionnaire was used to identify learning experiences in the Indonesian-English translation class using PBL. Respondents were students of the 6th semester of the English language education program who took part in the English-Indonesian translation course. Data is presented in the form of descriptive explanations and also supported by graph data to facilitate the presentation. This study shows that the use of PBL provides benefits in forming independent learners, improving critical thinking and can improve attitudes in collaboration with peers. However, there are still obstacles and challenges in translation courses using PBL, namely at the beginning of the lecture in the form of less preparation time, adaptation with group mates and also the location of observations that are located some distance from the campus or where students are, and there are difficulties in translating cultural words found.Key words: PBL, Translation, Learning Experience